JAŃA TEXNOLOGIYALAR TIYKARÍNDA MOTOR ALALIYALÍ BALALARDÍŃ KOMMUNIKATIV KÓNLIKPELERIN QÁLIPLESTIRIW - Ajimova, Z.G. (ILIM hám JÁMIYET, 2025)
The article examines the main directions of developing communicative skills in children with motor alalia based on modern digital technologies. The possibilities of using AAC technologies, AR/VR platforms, and artificial intelligence are identified, and their effectiveness in the process of speech therapy correction and development is presented. Based on practical examples and experience, the conditions for implementing technologies demonstrate the importance of teacher training and working with families.